Estimación del potencial de energía eléctrica aprovechable de un grupo de bicicletas estáticas pertenecientes al Gimnasio Power House Gym, mediante el uso de un prototipo. - Jara Parra, Luis Eduardo (2019)
In the present project the times of utilization of the static bikes of the gym POWER HOUSE GYM were established, by means of the data collection and its later analysis, determining therefore the average period of use of the static bicycles that is of 4 hours and 12 minutes); being Saturday the day that less people use the bicycle; the average use of static bicycles is used for the "design of a 0.6 kW, electric propulsion and electric generation system. The technical characteristics of the generation system by human propulsion, its place of installation and its application are established, determining the parameters to be considered for the design: loads to be fed, system demand, energy consumption determined by lifting of flow, weight census and with the installation of a flow analyzer (Fluke 365) owned by the electricity company ELEPCO SA. The electrical calculations were made for the dimensioning of the generation system by human propulsion; it was obtained that it was necessary to install two batteries of 316Ah each one to be able to feed the demand of lighting of the gym, connected in a system of By Pass, that is to say while the battery 1 is feeding the flow, the second battery would be charging. Finally, connection diagrams and investment budget had been elaborated.